Gender differences in science performance among 8th grade Iranian students in TIMSS 2007. - Sahranavard, Maryam; Hassan, Siti Aishah (2012)
This study investigates the differences between male and female among 8th grade Iranian in science performance of the Trend International Mathematics and Science Study (TIMSS 2007). Changes in the average percent scores for science performance indicated a descending trend for both genders in the past few TIMSS cycles. Female students generally outscored male students in science, in particular, similar results were found for 8th grade Iranian students in TIMSS 2007. A total of 3981 8th grade students (1786 girls and 2195 boys) from Iran who participated in TIMSS 2007 were studied on their response to students’ questionnaire of TIMSS 2007. This study also explored the underlying constructs of students’ questionnaire items of TIMSS 2007 based on gender. Principal Component Analysis was performed to determine underlying constructs among the students’ questionnaire items. The results of principal component analysis showed that 21 items from the questionnaire were loaded into six factors for both genders with slight differences on the loadings. The underlying constructs were identified as students’ self-concept on efficacy-intrinsic motivation, extrinsic motivation, active and passive learning, self-defence and positive attitude on school climate.